Motif Berkarir di Sektor Pemerintah Bagi Mahasiswa IPDN - Zainal Abidin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
The purpose of this study was to determine the motives for a career in the government sector for IPDN students. This research uses qualitative method with phenomenology approach that aims to know the world from the point of view of the person who experienced it directly or related to the nature of human experience, and the meaning that is attached to it. The result of the research shows that their motives for a career in the government sector of IPDN students are divided into four motives, the first motive is the success of the closest person, second is the failure to become Indonesian Army and Indonesian Police Officer, third is economic limitations and the fourth is the improvement of social status.IPDN students have a positive self-concept. This is illustrated by how they view themselves, and how they view other students, both around their campus environment (Jatinangor) and generally in Indonesia. For them, non-IPDN students are not superior at all, even IPDN students tend to feel superior to general students, both academically and disciplined. Moreover, these students are very confident that they are indeed prepared to become leaders in the society.Keywords: Phenomenology, Motives, Career, IPDN Students.